Analysis of Ribavirin Mutagenicity in Human Hepatitis C Virus Infection - Chevaliez, Stéphane (American Society for Microbiology, 2007)
The addition of ribavirin to alpha interferon therapy significantly increases response rates for patients with chronic hepatitis C virus (HCV) infection, but ribavirin's antiviral mechanisms are unknown. Ribavirin has been suggested to have mutagenic potential in vitro that would lead to “error catastrophe,” i.e., the generation of nonviable viral quasispecies due to the increment in the number of mutant genomes, which prevents the transmission of meaningful genetic information. We used extensive sequence-based analysis of two independent genomic regions in order to test in vivo the hypothesis that ribavirin administration accelerates the accumulation of mutations in the viral genome and that this acceleration occurs only when HCV replication is profoundly inhibited by coadministered alpha interferon. The rate of variation of the consensus sequence, the frequency of mutation, the error generation rate, and the between-sample genetic distance were measured for patients receiving ribavirin monotherapy, a combination of alpha interferon three times per week plus ribavirin, or a combination of alpha interferon daily plus ribavirin. Ribavirin monotherapy did not increase the rate of variation of the consensus sequence, the mutation frequency, the error generation rate, or the between-sample genetic distance. The accumulation of nucleotide substitutions did not accelerate, relative to the pretreatment period, during combination therapy with ribavirin and alpha interferon, even when viral replication was profoundly inhibited by alpha interferon. This study strongly undermines the hypothesis whereby ribavirin acts as an HCV mutagen in vivo.